Mediasi Lingkungan Kerja Terhadap Budaya Organisasi Dalam Meningkatkan Kinerja Pegawai Biro Pemerintahan Dan Otonomi Daerah Sekretariat Daerah Provinsi Maluku - Heromike Jeni Maahury; Zainal Abidin Rengifurwarin; Elake Nataniel (Jurnal Ilmiah Global Education, 2026)
This study aims to analyze the effect of organizational culture on employee performance with the work environment as a mediating variable at the Bureau of Government and Regional Autonomy, Regional Secretariat of Maluku Province. The research employs a quantitative approach using a survey method. The population consists of all 64 employees of the institution, and a full sampling technique is applied. Data are collected through a closed-ended questionnaire measured using a Likert scale. Data analysis is conducted using Structural Equation Modeling based on Partial Least Squares with the SmartPLS application. The results indicate that organizational culture has a significant effect on employee performance and the work environment. Furthermore, the work environment has a significant effect on employee performance. The indirect effect test confirms that the work environment significantly mediates the relationship between organizational culture and employee performance. These findings suggest that improving employee performance is more effective when supported by a strong organizational culture and a conducive work environment. Therefore, strengthening organizational culture and enhancing the work environment are essential strategies for improving employee performance in local government institutions.